INTEGRASI PENDIDIKAN LINGKUNGAN DALAM PENGELOLAAN SAMPAH PLASTIK DAN PENGEMBANGAN EKONOMI KREATIF - Darni, Darni; Hayani, Nurrahmi; Illosa, Abdiana; Azizi, Fahri; Gusnia, Hety; Alfitra, Yolanda; Nadila, Pinky; Sadiva, Rezki Fitri (COMMUNITY SERVICE JOURNAL OF ECONOMICS EDUCATION, 2024)
The city of Pekanbaru faces significant challenges in managing plastic waste, which comprises 30%-40% of the total 1,500 tons of daily waste in 2022. Inadequate waste management infrastructure and low public awareness exacerbate this issue. This study explores the integration of environmental education and creative economy development as sustainable solutions. Through the Service-Learning methodology, the community is engaged in educational programs and the processing of plastic waste into value-added products, such as handicrafts. Results show increased awareness and participation in waste management, along with the emergence of new economic opportunities. Continuous guidance is needed to encourage households to segregate waste from the source. In conclusion, integrating environmental education and creative economy development can effectively address plastic waste issues in Pekanbaru, improve local economic welfare, and preserve environmental sustainability.